O cuidado nos territórios no contexto da pandemia : uma formação viva em ato - Lazaretto, Marina Pitágoras (2021)
In 2020, new events marked the world, especially in the area of health. A new virus crossed the “corners” of the world without asking permission, materializing in the Covid-19 pandemic. This situation affected all of our lives in different dimensions. Evidencing a civilizing and health crisis, different actors were summoned and had to build emergency strategies to deal with the diversity of challenges that were required by the pandemic. In high education, especially in health courses, movements were being made to call the Universities to their social commitment, particularly in working with the most vulnerable communities. Considering the context, this work seeks, in general, to understand the potential of a strategy to fight the pandemic as an innovative and qualifying movement for democratic and integral education in the area of health. The research has a qualitative design and is exploratory in nature. Data collection was based on the analysis of audiovisual materials produced during the execution of the project, which were anchored in the perspective of the quadrilateral of health education. The data underwent a qualitative discourse analysis, in order to understand the meanings of the lived experience. The analysis show the Covid-19 pandemic as an event laden with lessons, driven by the challenges imposed. Considering the aspects that guide the reorientation of health education, it is highlighted that the contact with the territory and with the people who make up these scenarios, as well as the formulation of training anchored in the perspective of an affective pedagogy and involved with the issues of life found outside the walls of the university, it is necessary and urgent to formulate invitations that integrate teaching-service-community and management to overcome and overcome the specificities that anchor training in health, and make the SUS a full and civilizing system.